2001
DOI: 10.1099/0022-1317-82-9-2169
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic variants with amino acid deletions clarify a neutralizing epitope specific for influenza B virus Victoria group strains

Abstract: To study the neutralizing epitopes of influenza B virus Victoria group strains, two monoclonal antibodies (MAbs) were used to select antigenic variants of the virus. MAbs 10B8 and 8E6 were found to react with B/Victoria group strains in three tests, peroxidase-antiperoxidase staining, haemagglutination inhibition and neutralization tests ; no reactivity with B/Yamagata group strains was observed. Analysis of the deduced amino acid sequences of 10B8-induced variants identified a single amino acid deletion at re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
25
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 17 publications
5
25
0
Order By: Relevance
“…At the same time, the escape mutant 9A3, in addition to the acquired resistance to the homologous mAb lost the ability to interact with the heterologous mAb 8H3. The analogous phenomenon has been described in the literature [17]. The authors showed that from the eight different escape mutants (V1 -V8) of virus B/Osaka/983/97 of Victorian lineage, selected with mAb 10B8, only two (V3 and V8), which have the amino acid substitution Lys→Thr at position 203 (202 according to the Yamagata numbering and 193 according to the H3 numbering), lost their ability to interact with the heterologous mAb 8E6.…”
Section: Selected Escape Mutants and Their Antigenic Propertiesmentioning
confidence: 60%
“…At the same time, the escape mutant 9A3, in addition to the acquired resistance to the homologous mAb lost the ability to interact with the heterologous mAb 8H3. The analogous phenomenon has been described in the literature [17]. The authors showed that from the eight different escape mutants (V1 -V8) of virus B/Osaka/983/97 of Victorian lineage, selected with mAb 10B8, only two (V3 and V8), which have the amino acid substitution Lys→Thr at position 203 (202 according to the Yamagata numbering and 193 according to the H3 numbering), lost their ability to interact with the heterologous mAb 8E6.…”
Section: Selected Escape Mutants and Their Antigenic Propertiesmentioning
confidence: 60%
“…Furthermore, with the recent B/Victoria isolates, other amino acid substitutions were observed in the "tip" of the HA molecule, where B/Victoria strain-specific epitope sites exist (8). Whether these sites affect viral antigenicities is now under investigation.…”
mentioning
confidence: 99%
“…Antigenic variants often show only a one-point nucleotide mutation, which results in one amino acid substitution (1,8,11). In this case, NET strains gained an N-linked glycosylation site in the vicinity of the epitope site of 8E6.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Site B and site A (a protruding loop region) of the HA molecule have been reported to be the highly immunodominant regions of influenza A and B viruses (1,17). We developed monoclonal antibodies (MAbs) 10B8 and 10D7, whose epitopes had been conserved at site B of B/Victoria isolates since the mid-1980s until the 1996/1997 season (7,9). However, the 2002/2003 isolates in Kobe, Japan, were divided into three groups according to their reactivities to 10B8 and 10D7.…”
mentioning
confidence: 99%